2013
DOI: 10.1002/adfm.201202926
|View full text |Cite
|
Sign up to set email alerts
|

Microfabricated Porous Silk Scaffolds for Vascularizing Engineered Tissues

Abstract: There is critical clinical demand for tissue-engineered (TE), three-dimensional (3D) constructs for tissue repair and organ replacements. Current efforts toward this goal are prone to necrosis at the core of larger constructs because of limited oxygen and nutrient diffusion. Therefore, critically sized 3D TE constructs demand an immediate vascular system for sustained tissue function upon implantation. To address this challenge the goal of this project was to develop a strategy to incorporate microchannels int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 50 publications
0
36
0
Order By: Relevance
“…Even highly porous scaffolds limit cell infiltration as demonstrated by the difficulty of evenly seeding scaffolds in vitro . To combat this issue, scaffolds have been designed with large, 250–500 micron diameter, arrayed channels to allow cells to quickly infiltrate deep within the scaffold (64). In vivo , these scaffolds had increased vascularization by 14 days post implant as compared to scaffolds without channels (32).…”
Section: Vascular Ingrowth Into Silk Materialsmentioning
confidence: 99%
“…Even highly porous scaffolds limit cell infiltration as demonstrated by the difficulty of evenly seeding scaffolds in vitro . To combat this issue, scaffolds have been designed with large, 250–500 micron diameter, arrayed channels to allow cells to quickly infiltrate deep within the scaffold (64). In vivo , these scaffolds had increased vascularization by 14 days post implant as compared to scaffolds without channels (32).…”
Section: Vascular Ingrowth Into Silk Materialsmentioning
confidence: 99%
“…Recent studies have revealed the feasibility of silk as a supporting matrix for cells, including fibroblasts, osteoblasts, hepatocytes, nerve and stem cells, as well as a scaffolding for tissue engineering of bone, ligaments, blood vessels, skin, cartilage and other tissues [711]. Following the increasing applications, there remains a demand to further improve the bioactivity of silk scaffolds.…”
Section: Introductionmentioning
confidence: 99%
“…By diffusion alone, thick scaffolds can only sustain cells within a few hundred μm of the liquid-scaffold interface in vitro , a limitation which is closely approximated in vivo [2,3]. Various techniques to improving vascular conduction have been studied [4], including use of growth factors [57], bioactive materials [8,9], microfabrication [1012], angiogenic cells [1315], decellularized organs with intact microvasculature [16,17], non-biological factors [18], and even oxygen-producing biomaterials [19]. Microfabrication is especially important since improved conduction pathways can accelerate or improve other efforts to increase angiogenesis in implants [20].…”
Section: Introductionmentioning
confidence: 99%